Indonesia and the Netherlands cooperation strategy in the football player naturalization program: implications for the development of Indonesian football (2019 – 2024) - Muhammad Rifki Maulana, Rifki; Gonda Yumitro, Gonda (Rumah Jurnal, University of Jember, 2025)
The naturalization of football players has emerged as a strategic approach adopted by various countries to enhance the competitiveness of their national teams on the international stage. Indonesia, which shares a historical relationship with the Netherlands, has leveraged this connection by collaborating to identify and recruit football players of Indonesian descent who are active in European leagues. This study aims to analyze the strategic partnership between Indonesia and the Netherlands in implementing the football player naturalization program and to examine its implications for the development of Indonesian football. Employing a descriptive-qualitative method with a case study approach, the research draws on secondary data sources such as theses, journals, and relevant scholarly articles. The findings indicate that the program has significantly improved the quality of the national team and revitalized historical and cultural ties between the two nations. Nevertheless, several challenges persist, including public resistance, debates on nationalism, and administrative hurdles in the naturalization process. To ensure long-term benefits for Indonesian football, this study recommends a more strategic and sustainable policy framework that balances naturalization efforts with the development of local talent.